Lipid Bilayers Covalently Anchored to Carbon Nanotubes - Dayani, Yasaman (2012)
The unique physical and electrical properties of carbon nanotubes make them an exciting material for applications in various fields such as bioelectronics and biosensing. Due to the poor water solubility of carbon nanotubes, functionalization for such applications has been a challenge. Of particular need are functionalization methods for integrating carbon nanotubes with biomolecules and constructing novel hybrid nanostructures for bionanoelectronic applications. We present a novel method for the fabrication of dispersible, biocompatible carbon nanotube-based materials. Multi-walled carbon nanotubes (MWCNTs) are covalently modified with primary amine-bearing phospholipids in a carbodiimide-activated reaction. These modified carbon nanotubes have good dispersibility in nonpolar solvents. Fourier transform infrared (FTIR) spectroscopy shows peaks attributable to the formation of amide bonds between lipids and the nanotube surface. Simple sonication of lipid-modified nanotubes with other lipid molecules leads to the formation of a uniform lipid bilayer coating the nanotubes. These bilayer-coated nanotubes are highly dispersible and stable in aqueous solution. Confocal fluorescence microscopy shows labeled lipids on the surface of bilayer-modified nanotubes. Transmission electron microscopy (TEM) shows the morphology of dispersed bilayer-coated MWCNTs. Fluorescence quenching of lipid-coated MWCNTs confirms the bilayer configuration of the lipids on the nanotube surface and fluorescence anisotropy measurements show that the bilayer is fluid above the gel-to-liquid transition temperature. The membrane protein α-hemolysin spontaneously inserts into the MWCNT-supported bilayer, confirming the biomimetic membrane structure. These biomimetic nanostructures are a promising platform for the integration of carbon nanotube-based materials with biomolecules.